Grading the College : A History of Evaluating Teaching and Learning - Gelber, Scott M. (Book collections on Project MUSE., 2020)
"This book dispels the common impression that evaluating and ranking colleges and universities began only a few decades ago. Focusing on the era between 1920 and 1980, this book demonstrates that administrators, foundations, and scholars have wrestled with the challenges of evaluating higher education institutions for nearly a century. Professors contributed to the development of evaluation instruments such as student surveys and standardized tests"--